Civil war in Libya in years 2014–2018 (Economic and Political Thought, 2019)
Libya is a country plunged in chaos. Fighting is ongoing in many regionsin the North. In the north-western part of the country a strong position isheld by coalition of Islamists. The political situation in Libya is extremelycomplicated. On the 18th December 2015 the members of the House ofRepresentatives and the General National Congress signed a Libyan PoliticalAgreement. As a result a Presidential Council and the Governmentof National Accord (GNA) were created. The House of Representativesstill exists as a legislative body and the Advisory Board, known as the HighCouncil of State. In fact, the Libyan Government is still divided between theHouse of Representatives and a General National Congress (GNC), as twoseparate governments. One of them – the House of Representatives, has itsheadquarters in Tripoli, the capital that is controlled by the Islamists, whilethe second is a General National Congress, in Tobruk.
Keywords: civil war in Libya, military conflict, jihadism, Gaddafi, Libya